PENGARUH PENERAPAN MEDIA AUGMENTED REALITY BERBASIS DISCOVERY LEARNING TERHADAP HASIL BELAJAR PADA MATERI DARAH - Purnamasari, Dian; Sudarisman, Suciati; Dwiastuti, Sri (Universitas Sebelas Maret, 2016)
The research was aimed to ascertain the influence of application augmented reality media based discovery learning toward learning achievement. The research was quasi experimental research, using post-test only with non-equivalent groups. The population was all students of XI IPA MAN 2 Surakarta in Academic Year 2014/2015, which is divided into 3 classes. The sampling technique used in the research was a cluster sampling. Sample was used class XI IPA 2 consist of 22 siswa for control class with image media with konvensional learning ang class XI IPA 1 consist of 22 siswa for experiment class with augmented reality media based discovery learning. The data were collected using tests and non-tests techniques. Tests techniques using tests method multiple choice and short essay to measure learning achievement in knowled domain, while non-test techniques observation method using observation sheet to measure learning achievement in skills domain and attitude domain. The hypothesis was analyzed with t-test and mann-whitney test using SPPS version 16. The result showed learning achievement knowledge domain (Sig. 0,000 < 0,05), skills domain (Sig. 0,003 < 0,05), and attitude domain (Sig. 0,008 < 0,05). Based on the result to indicate signification of learning achievement < 0,05 so there were difference effects of application augmented reality media based discovery learning with konvensional learning toward learning achievement.Â Keywords: augmented reality media, discovery learning, learning achievement.